2019
DOI: 10.5603/gp.2019.0047
|View full text |Cite
|
Sign up to set email alerts
|

A study of physical activity levels of pregnant women using the Polish version of Pregnancy Physical Activity Questionnaire (PPAQ-Pl)

Abstract: Objectives:The aim of the present study was to determine the optimal level of physical activity during pregnancy and discuss whether and to what extent biological, social and demographic variables affect the level of total physical activity in studied women. Material and methods:The respondents were 267 pregnant women from Poland aged 28.16 ± 4.67 years. The majority of women under study had a higher and a secondary education and lived in villages near Poznań, i.e. a large urban agglomeration in Poland. Most o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 20 publications
(25 reference statements)
4
16
1
Order By: Relevance
“…These data are consistent with pooled worldwide data showing that the prevalence of physical inactivity is twice as high in higher compared with lower income countries [12]. The median of the total energy expenditure among pregnant women in this study is in the range of the reported mean/median total energy expenditure among pregnant women in previous studies from different countries, ranging from 123.2 METs*hour/week in Vietnam to 270.9 METs*hour/week in Portugal [16,18,27,[42][43][44]. At 183.3 METs*hour per week, the median total energy expenditure value in this study is almost the same as the findings among urban pregnant women in the state of Selangor, which surrounds the federal city of Kuala Lumpur geographically [45].…”
Section: Discussionsupporting
confidence: 91%
“…These data are consistent with pooled worldwide data showing that the prevalence of physical inactivity is twice as high in higher compared with lower income countries [12]. The median of the total energy expenditure among pregnant women in this study is in the range of the reported mean/median total energy expenditure among pregnant women in previous studies from different countries, ranging from 123.2 METs*hour/week in Vietnam to 270.9 METs*hour/week in Portugal [16,18,27,[42][43][44]. At 183.3 METs*hour per week, the median total energy expenditure value in this study is almost the same as the findings among urban pregnant women in the state of Selangor, which surrounds the federal city of Kuala Lumpur geographically [45].…”
Section: Discussionsupporting
confidence: 91%
“…In addition, age, the number of children, stage of pregnancy, and lower level of education, and employment status significantly influenced the level of physical activity during pregnancy in Africa [59,85,86,98,104,109]. This proved consistent with other studies that reported age [120], low education [53,57,121], pregnancy trimester [122,123], and employment [121] as correlates affecting physical activity during pregnancy. Women who attain higher level of education are more knowledgeable about PA during pregnancy [48,59].…”
Section: Discussionsupporting
confidence: 87%
“…However, our finding demonstrated from the predictive model that pregnant women who commence physical activity in the first trimester are significantly more likely to be physically active during pregnancy compared to those who start later than the second trimester. This is concordant with a study in Poland [61], and USA [15] which found the odds of meeting physical activity recommendations, including both moderate and vigorous activities, to be higher among women in the first trimester compared to the third trimester. However, our finding is inconsistent with the findings from other previous studies, which indicated that women in the third trimester were more likely to meet the physical activity guideline compared to those in the first trimester [17,54,65,74,75].…”
Section: Discussionsupporting
confidence: 88%
“…Conversely, in Hailemariam et al [13] study in Ethiopia it was reported that women who were 26-35 years were 2.69 times more likely to be sedentary (AOR: 2.69, 95% CI: 1.07-6.78) compared with those in the age category of 16-25 years. Similar studies have reported age as a predictor of prenatal active practice [21,61].…”
Section: Discussionsupporting
confidence: 64%